Factor Analysis of the Morphostructure of Mature Balami Sheep (2010)
Ten body measurements were taken on 100 Balami sheep aged 18-24 months within the humid southwest Nigeria. The body measurements were Wither Height (WH), Body Length (Bl), Rump Height (RH), Rump Width (RW), Rump Length (RL), Shoulder Width (SW), Tail Length (TL), Heart Girth (HG), Neck Circumference (NC) and Body Weight (BW). The study was aimed at investigating the variance structure and to provide a description of the conformation of the sheep using a cluster analysis. Applying wither height for size estimation, the animal measured 83.96±5.99 cm. The other body measurements for the age group were BL = 96.06±11.45 cm, RL = 28.13±5.19cm,RW = 23.14±2.07 cm, RH = 87.18±5.99cm, SW = 27.85±4.37 cm, TL = 57.56±4.56 cm, HG = 95.68±5.31 cm, NC = 41.26t8.36cm and BW = 53.01±9.50kg. Variability was high within body measurements